The career and works of Samuel Harsnett, Archbishop of York, 1561-1631 - Pearce, M (2004)
﻿ This thesis provides a study of the career and works of Samuel Harsnett, one of the most senior members of the early Stuart Church. Harsnett enjoyed a distinguished career as bishop of Chichester and Norwich, and finally as archbishop of York, but earned notoriety much earlier, by virtue of preaching a controversial sermon against the then orthodox Calvinist position on predestined grace. It was this early expression of anti-Calvinism (or Arminianism as it later became termed), together with a predisposition towards tradition on the liturgy and ceremony of the Church, which has earned Harsnett, as Conrad Russell put it, a place among "the cream of the English Arminians". As the first future bishop to express openly anti-Calvinist views Harsnett's career is contemporaneous with the first forty years of what Nicholas Tyacke described as the 'Rise of Arminianism'. For that reason he is deserving of a biographical study, both to determine the nature of Arminianism in practice and his particular contribution to its 'Rise'. In seeking to determine Harsnett's contribution to the Arminian phenomenon this thesis suggests that Harsnett was, in a number of respects, hardly the archetypal Arminian that Professor Russell and most other modern historians have assumed. This raises important questions as to the actual significance of the theology of predestination to developments in the early Stuart Church. The significant areas of Harsnett's career considered in the thesis are: his formative years as a scholar and then fellow at Pembroke College, Cambridge; his early career as chaplain to Richard Bancroft when Harsnett probably developed his lifelong dislike of Puritan non-conformity; his episcopal career at Chichester and then Norwich; his parliamentary career, which was marked by major ideological differences with fellow Arminians; his final appointment as archbishop of York, senior religious adviser to the king and Privy Councillor.